Dauru Kafa'ati Thullab Kuliyyah Al-Syari'ah Jami'ah Pekalongan Al- 'Islamiyyah Al-Hukumiyah 'Ala Al-Lughah Al-'Arabiyyah Fi Ta'liimi Ushul Fiqh - Ade Dedi Rohayana (Jurnal Alsinatuna, 2017)
This study is aims to know the role of Arabic competence in ushul fiqh teaching and learning of students of sharia faculty in Pekalongan State Islamic Institution. This qualitative research uses descriptive method. Ushul fiqh is one of the compulsory subjects for students of sharia faculty. The students' ability in Arabic has an important role in understanding ushul fiqh cases that is islamic proposition used in deciding laws. This islamic proposition is based on Koran and Hadith. To understand this islamic proposition, they need Arabic. Beside that, lots of terminologies in ushul fiqh take source from arabic laguage. Sharia faculty’s students learn the language in Intensive Arabic class in the 1st year of their study in Pekalongan State Islamic institute.